Beyond Emergency: Charting Pathways to Sustainable Development in Fragile and Conflict-Affected Settings: A Case Study of Yemen - Alsahbool, Sharif Abdurabu Salem Farid (AUC Knowledge Fountain, 2026)
For nearly a decade, Yemen's eastern governorates of Hadramawt, Shabwah, and Al‑Mahrah have been relatively stable, yet the international aid system has kept delivering short‑term humanitarian relief like food baskets and water trucking instead of shifting to sustainable development that could rebuild people's lives, create jobs, fix infrastructure, and strengthen local government. This thesis investigates why this transition has taken so long. Based on 21 interviews with government officials, international NGO staff, and local NGO managers in these three governorates, the study develops a new way of understanding the problem. It introduces three ideas: the 'emergency mentality', which is a deep‑rooted habit of treating every crisis as if it just started; 'transitional intent', which measures whether a project actually builds something that lasts; and 'fragile stability', which describes places that are not at war but also do not have a functioning state. The findings reveal a stark manifestation of what the literature calls the "two worlds" problem, where humanitarian and development mandates, funding streams, and organisational cultures remain separate, actively blocking a genuine transition to sustainable development. Between 2016 and 2020, almost all aid was emergency relief, even though these areas were not war zones. Between 2021 and 2023, change was very slow. Only after 2024 did things start to move, and that was mainly because donors cut funding due to other crises in Ukraine, Sudan, and Gaza, not because of a smart plan to support sustainable development. The research uncovers many barriers that block the path to sustainability: old and exaggerated data, private donors who demand the same old food baskets every year, organisations that benefit from keeping the emergency going, local groups locked out because they lack experience, and widespread corruption. But the research also finds real success stories. When donors were flexible, when communities came up with their own solutions, when local governments helped pay for projects, and when designs integrated training and handover to local people, sustainable development happened even in these difficult conditions. This thesis makes four original contributions to the field of sustainable development. First, it shows that the 'emergency mentality' is not just a bad habit but a system problem caused by donor rules, copying between organisations, and career rewards that favour fast relief over lasting change. Second, it offers a new tool called 'degrees of sustainability', ranging from ten percent to one hundred percent, so that donors and agencies can see that moving from food baskets to community gardens is progress, even if it is not perfect. Third, it builds on the idea of the 'Empty State' to explain that when the government is hollow and weak, aid groups have no real partner to work with, so they fall back on quick fixes. Fourth, it charts actionable pathways for sustainable development, offering practical advice for donors, UN agencies, governments, and local NGOs. The message is clear: waiting for perfect peace is a mistake. Sustainable development can and must start now, inside the mess of fragile stability. This thesis shows how. Keywords: Humanitarian-development nexus; emergency mentality; transitional intent; fragile stability; Yemen; protracted crisis; aid effectiveness; sustainable development